2022
DOI: 10.1039/d1sc05753g
|View full text |Cite
|
Sign up to set email alerts
|

High-efficiency hyperfluorescent white light-emitting diodes based on high-concentration-doped TADF sensitizer matrices via spatial and energy gap effects

Abstract: A thermally activated delayed fluorescence host was developed to realize high-efficiency fluorescence white organic light-emitting diodes (WOLED) through spatial and energy gap effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…Therefore, searching for and using new WOLEs are of particular interest. Recently, hybrid-WOLEDs with blue thermally activated delayed fluorescence (TADF) materials have become an alternative approach that enables the harvesting of both singlet and triplet excitons for light emission. It is well known that TADF materials can harvest triplet excitons through a reverse ISC (RISC) process from the triplet state to the singlet state due to the low Δ E ST value (typically <0.5 eV). Based on the TADF mechanism, few TADF-based WOLEDs are reported, where multiple emissive layers are used to modify exciton allocation by spatially separating two or more host-dopant systems of different emission colors. ,,, Hence, the development of white OLEs (WOLEs) based on TADF that can achieve high efficiency is of great importance. Therefore, if WLE based on multiple TADF emitters with frustrated energy-transfer mechanisms could be achieved, the materials would create new opportunities in WOLEDs due to the light emission of two or three colors in a single emissive layer (EML).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, searching for and using new WOLEs are of particular interest. Recently, hybrid-WOLEDs with blue thermally activated delayed fluorescence (TADF) materials have become an alternative approach that enables the harvesting of both singlet and triplet excitons for light emission. It is well known that TADF materials can harvest triplet excitons through a reverse ISC (RISC) process from the triplet state to the singlet state due to the low Δ E ST value (typically <0.5 eV). Based on the TADF mechanism, few TADF-based WOLEDs are reported, where multiple emissive layers are used to modify exciton allocation by spatially separating two or more host-dopant systems of different emission colors. ,,, Hence, the development of white OLEs (WOLEs) based on TADF that can achieve high efficiency is of great importance. Therefore, if WLE based on multiple TADF emitters with frustrated energy-transfer mechanisms could be achieved, the materials would create new opportunities in WOLEDs due to the light emission of two or three colors in a single emissive layer (EML).…”
Section: Introductionmentioning
confidence: 99%
“…Phosphine oxide with strong electron-withdrawing effect is promising as an acceptor for the building of TTA emitters. Recently, in 2021, Rajamalli et al reported two bipolar green TTA emitters ( 41 and 42 ) by decorating them with an electron-transporting phosphine oxide unit and electron-donating tolylamine and carbazole units (Scheme ). Compounds 41 and 42 exhibited green emission peaks at 520 and 522 nm in toluene, accompanied by the high PLQYs of 63%–68% in toluene and 84%–87% in the neat films, respectively.…”
Section: Triplet–triplet Annihilation Materials and Oledsmentioning
confidence: 99%
“…Inspired by this method, more APO-based emitters with improved rigidity have been reported. 32,42,[44][45][46][47][48][49] Among the APO-type moieties, the 9-phenyl-9-phosphafluorene oxide (PhFIOP) group can possess inherent advantages of a highly rigid structure to furnish improved opto-electronic properties. Recently, we have introduced electron-donors to the 2-and 8-positions of the PhFIOP unit to construct new green TADF emitters showing high electroluminescence (EL) efficiencies of 23.3%, 83.7 cd A À1 , 59.1 lm W À1 for Z ext , Z L , and Z P , respectively, indicating its great potential for developing highly efficient TADF emitters.…”
Section: Introductionmentioning
confidence: 99%